Mutational landscape of circulating tumor DNA identifies distinct molecular features associated with therapeutic response in patients with metastatic colorectal cancer - Shi, Min; Yuan, Hong; Ji, Jun; Zhang, Shouwei; Li, Qingyuan; Chen, Yawei; Gong, Xiaoli; Zhu, Zhenggang; Zhang, Jun (Therapeutic advances in medical oncology, 2022)
Background: We investigated the mutational landscape of circulating tumor DNA (ctDNA) in predicting tumor response to first-line treatment in patients with metastatic colorectal cancer (mCRC). Methods: We included 41 patients with initially unresectable mCRC, treated with 5-fluorouracil/leucovorin/oxaliplatin (FOLFOX)/5-fluorouracil/leucovorin/irinotecan (FOLFIRI) with/without bevacizumab (Bev)/cetuximab (Cet). Blood samples were prospectively collected at two timepoints: at baseline and after four cycles of first-line treatment. Mutational status of 1086 genes were studied in ctDNA by targeted next-generation sequencing (NGS). Molecular mutational burden (MMB) was defined as mean mutation frequency among obtained mutations for each gene. To evaluate the association between molecular characteristics of cfDNA and therapeutic response better, we divided these patients into MMB-high and MMB-low group according to the median value of MMB (0.3). Results: Among the 41 enrolled patients, alterations of six genes (TRIM24, SPEN, RNF43, PRKAR1A, KRAS, and KDM5 C) were found at baseline. Baseline MMB of six genes was significantly lower in partial response (PR)/stable disease (SD) patients than progression disease (PD) patients (p = 0.0012). Further analysis demonstrated that genomic profiling of ctDNA from pretreatment blood samples was significantly different between PR/SD (non-PD) group and PD group. By comparing the baseline levels of KRAS MMB in the two subgroups, we found that PD cases were all MMB-high, whereas non-PD cases were mainly in MMB-low subgroup. Furthermore, patients with low-KRAS MMB had superior response rate, significantly longer progression-free survival (PFS) and longer overall survival (OS) than high-KRAS MMB group. Conclusions: This prospective and serial genomic profiling study revealed the utility of ctDNA in predicting clinical outcomes in mCRC patients under first-line treatment. Levels of KRAS MMB might aid in monitoring therapeutic efficacy in mCRC patients at pretreatment/after four cycles of first-line treatment.